Recyclable and reusable ionic liquid-supported azo precursors in Mitsunobu reactions. Issue 11 (1st March 2022) - Lin, Cheng-Kun; Lee, Wei; Wu, Chun-Fu; Shih, Fang-Yi
Abstract : The presented work describes the first combination of a new and stable form of ionic liquid supported azo precursors and a terminal oxidant that show high reactivity toward Mitsunobu reactions. Abstract : A new type of azo precursor, ionic liquid-supported hydrazidecarboxylate, was synthesized and applied in Mitsunobu reactions. The developed reagent is recyclable during the reaction and reusable after recovery by the ionic liquids. The ionic liquid-based azo precursor in conjugation with PhI(OAc)2 has been proved to be useful in the formation of carbon–oxygen, carbon–nitrogen, and carbon–sulfur bonds.